From the Editor - Vrček, Neven (Journal of Information and Organizational Sciences, 2013)
Dear authors, readers and future authors, it is my pleasure to present you the 2nd number of the 37th volume of the Journal of Information and Organizational Sciences – JIOS. In this issue a selection of 3 original scientic papers and 2 preliminary communications has been included, all of which have undergone a rigorous double-blind review process in some cases in several rounds. The mission of JIOS is to cover scientic publications from broad area of information sciences and related disciplines and we continuously receive many articles in which authors strive to achieve scientic merit. Our review procedure is very strict but even when we decline papers we try to encourage authors in their future work and motivate them to give better results. That is why we maintain very good relations with our authors and we invite all of you to extend cooperation with JIOS. We hope that the variety of themes will draw the attention of researchers in dierent elds of information sciences and motivate potential authors to expand the Journal’s thematic scope by other themes that may be of interest to the wider ICT research community. These themes motivate us to continue our work of delivering research results to interested audience. The ICT eld is changing rapidly and we are constantly searching for cutting edge articles that open perspective and motivate further research. We have to notice that future of ICT related research is in interdisciplinary approach and relations with other research domains which is highly emphasized in Horizon 2020 directions. That is why we encourage and promote scientic collaboration across scientic areas that will bring us new interesting articles. We hope that many of you who will read the Journal will join us as authors, readers and reviewers and help us to fulll our mission. The number of submitted papers increases every year giving us opportunity to increase the quality and visibility of JIOS. I would like to use this opportunity to encourage prospective authors among you, dear readers, to submit papers at http://jios.foi.hr. You are also invited to share with us your comments or critical remarks regarding the papers previously published in the Journal. Further, we would appreciate your willingness to become a reviewer for submitted papers and thus contribute signicantly to the rising quality of JIOS. So far JIOS has been indexed in nine well known databases and we are proud to announce that from this issue we are indexed in two more databases Index Copernicus and Directory of Research Journals Indexing. We are continuously investing a lot of eort to extend the list of databases where JIOS would be cited, in order to make the published papers available to a larger readers’ audience, and give your research a greater impact factor.